Organiser la proximité entre usagers de l’eau : le cas de la Gestion Volumétrique dans le Bassin de la Charente - Céline Granjou; Patrice Garin (Développement Durable et Territoires)
Since the 90’s in the French region watered by the river Charente water resources have been weighed down with irrigation. In order to reduce conflicts which are linked to this situation, «Volumetric Management » introduces some new rules for irrigation practices including consultation. We propose to make a sociological assessment of the Volumetric Management basing on the notion of proximity with its different meanings. Several interviews with water users (farmers which use or don’t use water, fishers, residents, actors responsible for tourism…) show that a new proximity due the share of organisation rules has been developed, but that this proximity is: asymmetric because it privileges links between partisans of irrigation; instrumental because it lacks a commune long-term vision of territorial development; at last partial because the different interdependencies induced by the same water resource are not considered.